Effects of Water Availability on the Relationships Between Hydraulic and Economic Traits in the Quercus wutaishanica Forests - Zhang, Yuhan; Zhao, Jiale; Xu, Jinshi; Chai, Yongfu; Liu, Peiliang; Quan, Jiaxin; Wu, Xipin; Li, Cunxia; Yue, Ming (Frontiers in Plant Science, 2022)
Water availability is a key environmental factor affecting plant species distribution and the relationships between hydraulic and economic traits are important for understanding the species’ distribution patterns. However, in the same community type but within different soil water availabilities, the relationships in congeneric species remain ambiguous. In northwest China, Quercus wutaishanica forests in the Qinling Mountains (QM, humid region) and Loess Plateau (LP, drought region) have different species composition owing to contrasting soil water availability, but with common species occurring in two regions. We analyzed eight hydraulic traits and five economic traits of congeneric species (including common species and endemic species) in Q. wutaishanica forests of QM and LP. We explored whether the congeneric species have different economic and hydraulic traits across regions. And whether the relationship between hydraulic and economic traits was determined by soil water availability, and whether it was related to species distribution and congeneric endemic species composition of the same community. We found that LP species tended to have higher SD, VD, WSGbranch, Al: As, SL, ΨTlp and Vdmax than QM species. There was a significant trade-off between hydraulic efficiency and safety across congeneric species. Also, the relationships between hydraulic and economic traits were closer in LP than in QM. These results suggested that relationships between hydraulic and economic traits, hydraulic efficiency and safety played the role in constraining species distribution across regions. Interestingly, some relationships between traits changed (from significant correlation to non-correlation) in common species across two regions (from LP to QM), but not in endemic species. The change of these seven pairs of relationships might be a reason for common species’ wide occurrence in the two Q. wutaishanica forests with different soil water availability. In drought or humid conditions, congeneric species developed different types of adaptation mechanisms. The study helps to understand the environmental adaptive strategies of plant species and the results improve our understanding of the role of both hydraulic and economic traits during community assembly.